2011
DOI: 10.1177/1748007810394557
|View full text |Cite
|
Sign up to set email alerts
|

Remaining useful life, technical health, and life extension

Abstract: Life extension has for a long time been an important and highly discussed issue in nuclear and aviation industries, and has recently attracted considerable attention in the subsea oil and gas industry. Decision-making related to life extension is a multidisciplinary problem, but it primarily depends on the remaining useful life. This paper clarifies the concepts of remaining useful life and technical health, and discusses various influencing factors. An overall model with the capability to handle a heterogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 50 publications
0
39
0
4
Order By: Relevance
“…The paper suggested Bayesian Belief Network (BBN) as a useful technique for RUL estimation. Vaidya and Rausand (2011) proposed a LE decision making model based on RUL prediction by combining heterogeneous requirements such as degradation modelling, uncertain environmental and operational conditions, uncertain sensor data and expert judgement. The study further concluded that a physics-based approach is the most appropriate technique for supporting LE decision making in the offshore oil and gas industry.…”
Section: Physics-based Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper suggested Bayesian Belief Network (BBN) as a useful technique for RUL estimation. Vaidya and Rausand (2011) proposed a LE decision making model based on RUL prediction by combining heterogeneous requirements such as degradation modelling, uncertain environmental and operational conditions, uncertain sensor data and expert judgement. The study further concluded that a physics-based approach is the most appropriate technique for supporting LE decision making in the offshore oil and gas industry.…”
Section: Physics-based Approachmentioning
confidence: 99%
“…3) What type of integrity management programme needs to be put into place to support asset operations over the life extension period? In order to provide appropriate answers to above questions, Vaidya and Rausand (2011), Animah et al (2016) and Shafiee et al (2016) suggested, in their respective studies, that it is vital for LE decision makers to estimate the remaining useful life (RUL) of their candidate equipment, as it will enable stakeholders to achieve accurate conclusions during the LE decision-making process. Also, Liao et al (2006) suggested that when ageing degradation is detected, it is important to re-estimate the RUL in order to expedite urgent maintenance decisions and avert possible failures.…”
Section: Introductionmentioning
confidence: 99%
“…For a successful implementation of the LE management process, a multi-disciplinary decision-making methodology is required to develop (Vaidya and Rausand, 2011). This is because achieving an efficient LE solution requires inputs from all stakeholders, including designers, system engineers, manufacturers, material specialists, operators and maintenance technicians, health and safety professionals, financial and economic analysts, and human factor researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Hokstad et al (2010) proposed a framework for LE process, integrating material degradation, obsolescence and organisational issues to ensure acceptable technical integrity of offshore assets throughout their life extension period. Vaidya and Rausand (2011) proposed a model for technical health assessment of critical assets for LE and applied it to a subsea raw seawater injection system. Liu et al (2014) presented a framework for managing LE of offshore oil and gas installations in Chaina's Bohai Bay field.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of prognostics is the accurate estimation of remaining useful life (RUL). Bo Sun et al [8] discuss the benefits of prognostics, and explain how the calculation of RUL is important for technical health determination and life extension [9] in the context of condition-based monitoring [10]. Degradation signals [11], [12] and deterioration models [13] have been used in combination with statistical methods for estimating the remaining useful life in prognostics.…”
mentioning
confidence: 99%